Pink around the rink - Kann, Victoria (New York Harper, 2010)
Pinkalicious's new ice skates are plain white, so before she takes them out on the ice she decides to color them with her cotton candy pink magic marker
Ages 4-8
2 13
Keywords: Ice skating -- Fiction; Pink -- Fiction